2005
DOI: 10.1111/j.1095-8312.2005.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-host specificity and evolutionary patterns of host switching in a clade of specialist bees (Apoidea: Diadasia)

Abstract: We examined the levels of pollen-host specificity in North American Diadasia (Hymenoptera: Apoidea), a clade of specialist bees. We analysed the scopal pollen loads of 409 individuals representing 25 of the 30 species of Diadasia that occur in North America. Each Diadasia species showed a preference for one of five plant families. However, the 25 species varied in their level of host specificity: the average percentage by volume of the preferred host in pollen loads ranged from > 99% to < 75%. In 17 of the 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 66 publications
10
86
0
6
Order By: Relevance
“…Most cases of host-plant variation involve shifts in the host-plant visited with little change in diet breadth. This pattern is consistent with previous studies on the evolution of host-plant associations in bees (Müller, 1996a;Sipes and Tepedino, 2005;Patiny et al, 2007;Larkin et al, 2008).…”
Section: Degree Of Host-plant Specializationsupporting
confidence: 93%
See 3 more Smart Citations
“…Most cases of host-plant variation involve shifts in the host-plant visited with little change in diet breadth. This pattern is consistent with previous studies on the evolution of host-plant associations in bees (Müller, 1996a;Sipes and Tepedino, 2005;Patiny et al, 2007;Larkin et al, 2008).…”
Section: Degree Of Host-plant Specializationsupporting
confidence: 93%
“…However, several studies showed that field records are not always reliable enough to confidently determine the host-plant range because field records rarely distinguish between pollen and nectar foraging (e.g. Westrich and Schmidt, 1986;Westrich, 1990;Müller, 1996a;Sipes and Tepedino, 2005;Timmermann and Kuhlmann, unpubl. data.).…”
Section: Host-plant Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, pollen analysis revealed the actual use of pollen resources and excluded nectar-only collection and other bee activities that were included in observation of bee visits. Sipes and Tepedino (2005) pointed out that bees visit a relatively large number of plant species because of their nectar rather than pollen production (e.g., in our case, probably Dianthus carthusianorum). Secondly, results of pollen analysis demonstrate that the bee visits were not limited to typical plant species of sand ecosystems but that they also utilise resources in the surrounding agricultural landscape.…”
Section: Observation and Pollen Records: Floral Resourcesmentioning
confidence: 85%